Another in need enhances prosociality and modulates frontal theta oscillations in young adults - Lavín, Claudio; Soto-Icaza, Patricia; López, Vladimir; Billeke, Pablo (Frontiers in Psychiatry, 2023)
Decision-making is a process that can be strongly affected by social factors. Evidence has shown how people deviate from traditional rational-choice predictions under different levels of social interactions. The emergence of prosocial decision-making, defined as any action that is addressed to benefit another individual even at the expense of personal benefits, has been reported as an example of such social influence. Furthermore, brain evidence has shown the involvement of structures such as the prefrontal cortex, anterior insula, and midcingulate cortex during decision settings in which a decision maker interacts with others under physical pain or distress or while being observed by others. Using a slightly modified version of the dictator game, we tested the hypothesis that the inclusion of another person into the decision setting increases prosocial decisions in young adults and that this increase is higher when the other person is associated with others in need. At the brain level, we hypothesized that the increase in prosocial decisions correlates with frontal theta activity. The results showed that including another person in the decision, setting increased prosocial behavior only when this presence was associated with someone in need. This effect was associated with an increase in frontocentral theta-oscillatory activity. These results suggest that the presence of someone in need enhances empathy concerns and norm compliance, raising the participants' prosocial decision-making. Key words: Decision-making; prosociality; empathy.In everyday life, there are several examples of decisions that could have direct consequences on others, such as deciding how much money to donate to charity, how much food to buy when there are supply problems, or whether to give back a wallet full of cash that has just fallen from someone's pocket. In all these cases, people may consider, to different extents, the consequences of their behavior on the wellbeing of others and themselves (1). This processing is crucially affected by the circumstances in which the